Serum Lactate, AST, ALT in Male Autistic Children in Bangladesh - Karim, Mahmuda; Begum, Shelina; Shahzadi, Shorifa (Journal of Bangladesh Society of Physiologist, 2016)
Background: Mitochondrial dysfunction has been found associated with abnormal brain bioenergetics resulting in autistic spectrum disorder (ASD) Objective: To assess serum lactate, AST, ALT in order to observe the mitochondrial dysfunction in male children with autistic spectrum disorder. Method: This case-control study was conducted in the Department of Physiology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from January, 2013 to December, 2013. Total 100 male children with age range 3-8 years were randomly selected, among which 50 were normal children and 50 were diagnosed autistic children. Autistic children were enrolled from the Parents Forum for autistic children in Dhaka and the control subjects were selected from normal school. Serum lactate, Aspartate Aminotransferase (AST) and Alanine Aminotransferase (ALT) were estimated in all children by standard laboratory method. Independent samplet test was used for statistical analysis. Results: All these biochemical parameter were found significantly higher (p<0.001) in ASD children. In addition, elevated levels of serum lactate, AST and ALT were found in 94%, 46%, and 30% of autistic children respectively. Conclusion: From the result of this study it can be concluded that mitochondrial dysfunction may occur in children with autistic spectrum disorder. Bangladesh Soc Physiol. 2015, December; 10(2): 56-60